2012
DOI: 10.3109/19396368.2011.651555
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptins and the control of gonadotrophin secretion

Abstract: Kisspeptins, the peptide products of the KiSS-1 gene, bind to the G protein coupled receptor 54 (GPR54). Since 2003, research has revealed the important role of kisspeptins in initiating puberty, timing puberty and regulating fertility in adulthood. Specific mutations in GPR54 gene cause either delayed/absent puberty or precocious puberty. The KiSS-1/GPR54 system stimulates the gonadotrophin releasing hormone (GnRH) neurons and is involved in the feedback regulation of the HPG axis by gonadal steroids. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…A similar synergistic effect on ovarian cycling occurred in response to combinations of food restriction and psychosocial stress in cynomolgus monkeys (792). Increased activity and decreased eating combine to inhibit kisspeptin or GnRH neurons in the hypothalamus, which leads to reductions in LH and estrogens (175,456,666). Whether the reduced estrogen secretion is related to the weaker anorectic effect in female rats compared with male rats (185) is unknown.…”
Section: Physiological Sex Differences In Disordered Human Eatingmentioning
confidence: 92%
“…A similar synergistic effect on ovarian cycling occurred in response to combinations of food restriction and psychosocial stress in cynomolgus monkeys (792). Increased activity and decreased eating combine to inhibit kisspeptin or GnRH neurons in the hypothalamus, which leads to reductions in LH and estrogens (175,456,666). Whether the reduced estrogen secretion is related to the weaker anorectic effect in female rats compared with male rats (185) is unknown.…”
Section: Physiological Sex Differences In Disordered Human Eatingmentioning
confidence: 92%
“…The results demonstrated that the kisspeptin levels of girls in the ICPP group prior to treatment were significantly higher than those of the other groups, which supports the hypothesis that kisspeptin is an activating effector of the HPG axis. Significant increases in Kiss-1 gene expression trigger the pulsed release of GnRH, activate the HPG axis and initiate pubertal development, thereby causing the occurrence of PP (10).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous administration of kisspeptins downregulates the hypothalamic-gonadal-pituitary (HPG) axis (26). Kisspeptin is a potent peptide that initiates luteinizing hormone (LH) release in male and female mice (27), in both prepubertal and adult rats (28) and in prepubertal donkeys (29).…”
Section: Discussionmentioning
confidence: 99%